Salivary biomarkers of oxidants and antioxidants for chronic renal disease in patients undergoing maintenance hemodialysis - Nazar Ali, Geehan; Sabri Yas, Layla ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The steady decrease in glomerular filtration rate is a hallmark of chronic kidney failure, culminating in elevated serum creatinine concentrations and blood uric nitrogen. Chronic renal failure patients, especially those on hemodialysis, are increasingly diagnosed with oxidative stress. This cross-sectional study sought to estimate oxidative and antioxidative salivary biomarkers (malondialdehyde and catalase) in chronic renal disease patients and compare them to healthy control subjects. This research was performed at Al-Sader Medical City in Al Najaf. There were 60 participants separated into two groups: 30 patients made up the first group, with chronic renal failure, who had hemodialysis. The second group comprised 30 healthy patients with no severe disease in their medical history. It was noted that there were more females than males in this study. The current results indicated a considerable disparity between the MDA value in the control and uncontrolled groups. The MDA value exhibited a greater magnitude in the uncontrolled group. Conversely, the CAT value indicated a statistically significant distinction between the uncontrolled and control groups, with the control group exhibiting a higher CAT value than the uncontrolled group. The primary cause of free radical production and enzymatic antioxidant losses is hemodialysis; this indicates that HD intensifies oxidative stress rather than alleviating it.